An algorithm for finding a common solution for a system of mixed equilibrium problem, quasi-variational inclusion problem and fixed point problem of nonexpansive semigroup - Min, Liu; Chang, Shih Sen; Zuo, Ping (My University, 2010)
In this paper, we introduce a hybrid iterative scheme for finding a common element of the set of solutions for a system of mixed equilibrium problems, the set of common fixed points for a nonexpansive semigroup and the set of solutions of the quasi-variational inclusion problem with multi-valued maximal monotone mappings and inverse-strongly monotone mappings in a Hilbert space. Under suitable conditions, some strong convergence theorems are proved. Our results extend some recent results in the literature.
Opuscula Mathematica
Keywords: nonexpansive semigroup; mixed equilibrium problem; viscosity approximation method; quasi-variational inclusion problem; multi-valued maximal monotone mappings; alpha-inverse-strongly monotone mapping